2020
DOI: 10.1016/j.anbehav.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and pre-emptive spatial cohesion in a social primate

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Leopards may infrequently hunt samangos in this habitat compared with other available mammals (Williams et al 2018), but it is uncertain where they are most frequently encountered on the landscape compared with eagles that are encountered more frequently (LaBarge et al 2020a). From a prey animal's perspective, encounters with a potential predator should elicit a response (including freezing or other cryptic reactions) even if the predator itself is not engaged in an attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leopards may infrequently hunt samangos in this habitat compared with other available mammals (Williams et al 2018), but it is uncertain where they are most frequently encountered on the landscape compared with eagles that are encountered more frequently (LaBarge et al 2020a). From a prey animal's perspective, encounters with a potential predator should elicit a response (including freezing or other cryptic reactions) even if the predator itself is not engaged in an attack.…”
Section: Discussionmentioning
confidence: 99%
“…visual cues or alarm calls) (Pays et al 2013). General wariness or risk perceptions of group members might influence how much of a group is monitoring the environment versus engaged in other activities (Hochman and Kotler 2007) or how close individuals are to their conspecifics (Frechette et al 2014;LaBarge et al 2020a). Both factors are hypothesized to limit the ability of individuals to personally collect information about potential risks (Fernández-Juricic and Kacelnik 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Samango monkeys may therefore modify their behavior at a given location based on the spatial memory of previous encounters. A recent study from our field site by LaBarge et al (2020) would appear to support this hypothesis, as they found that samangos pre-emptively increased spatial cohesion in response to eagle encounter risk. Our findings corroborate those of LaBarge et al (2020), albeit over a longer study period, and suggest that samango monkeys may overestimate risk in areas perceived as high risk and opt to "play it safe" by reducing neighbor distance in these areas (Bouskila & Blumstein, 1992).…”
Section: Discussionmentioning
confidence: 72%
“…Proximity between individuals may depend upon perceived levels of risk in the environment (LaBarge et al, 2020). From this perspective, the response of mountain gorillas to the presence and immediate proximity of tourists suggests that gorillas might perceive tourists as a risk.…”
Section: Discussionmentioning
confidence: 99%